TEACHER–STUDENT INTERACTION IN QUR’ANIC TAHFIZ LEARNING AT MAS MUALLIMIN UNIVA MEDAN - Amaluddin Amaluddin; M. Syukri Azwar Lubis (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This study aims to determine the forms of interaction between teachers and students in Qur’anic tahfiz learning at MAS Muallimin Univa Medan, as well as to identify the supporting and inhibiting factors in the interaction process. This study employed a qualitative approach with a field research design. Data collection techniques included observation, interviews, and documentation. The research subjects consisted of the headmaster, tahfiz teachers, and tahfiz students. Data analysis used the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The findings revealed that teacher-student interaction in Qur’anic tahfiz learning occurred intensively through talaqqi activities, muraja’ah, memorization submission, tajwid guidance, learning motivation, and Islamic character development. Tahfiz teachers applied humane, persuasive, and caring communication patterns that created a comfortable and conducive learning atmosphere for students. Positive interaction between teachers and students significantly influenced tahfiz learning, including increased memorization enthusiasm, learning discipline, self-confidence, consistency in muraja’ah, and the quality of students’ Qur’anic memorization. Supporting factors included a religious school environment, patient and communicative teachers, and routine tahfiz activities. Meanwhile, inhibiting factors included differences in students’ characters, lack of learning focus, the influence of social media, and limited learning time. Therefore, teacher-student interaction plays an important role in improving the quality of Qur’anic tahfiz learning.